2013
DOI: 10.1115/1.4024814
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Machinability of Epoxy Reinforced With Graphene Platelets

Abstract: The objective of this research is to study the effect of graphene platelet (GPL) loading on the machinability of epoxy-based GPL composites. To this end, micro-milling experiments are conducted on composites with varying GPL content and their results are contrasted against that of plain epoxy. The material microstructure is characterized using transmission electron microscopy and scanning electron microscopy methods. Chip morphology, cutting force, machined surface morphology, and tool wear, are employed as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…When the GNP content exceeds 0.3 wt%, GNP agglomeration will happen in the matrix material. Arora et al [29] observed microcracks/fragments which were caused by the tool feed at the GNP agglomeration regions. The microcracks around the GNP agglomeration regions caused changes to the cracks on the machined surface.…”
Section: Surface Morphologymentioning
confidence: 99%
See 3 more Smart Citations
“…When the GNP content exceeds 0.3 wt%, GNP agglomeration will happen in the matrix material. Arora et al [29] observed microcracks/fragments which were caused by the tool feed at the GNP agglomeration regions. The microcracks around the GNP agglomeration regions caused changes to the cracks on the machined surface.…”
Section: Surface Morphologymentioning
confidence: 99%
“…This increase in lubrication properties may have cancelled out the effect of the increased overall strength and modulus of the epoxy/GNP nanocomposites. Another factor is that the presence of regions of GNP agglomeration means that the cutting force declines with increased GNP content [29]. The increase in cutting force is caused by overall strength and modulus.…”
Section: Cutting Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, less damage occurs during drilling leading to lesser delamination [21]. Another reason for a decrease in delamination on addition of MWCNTs can be attributed to the fact that the chip formation is aided when MWCNTs are added, due to the formation of nanotube agglomerates causing less friction between the tool edge and CFRP laminates [43]. …”
Section: Validation Testmentioning
confidence: 99%